Levels of dioxide of sulphur in La Oroya city historical analysis and perpectives - Plasencia Sánchez, Edson (2009)
In this paper the sulfur dioxide levels recorded in the environmental station called “Sindicato de Obreros” of the Metallurgical Complex of La Oroya (CMLO, by its spanish acronyms ) was analyzed between January 1998 to January 2009. This station has the longest historical record and shows an intermediate level of sulfur dioxide concentrations in front of the others stations of CMLO Environmental Monitoring Network, although, its concentrations frequently exceeded the maximum amount allowed by Peruvian environmental standards. Even assuming that due to the resumption of its operations, the Metallurgical Complex of La Oroya will produce (and will emit) as like its historical lows (1998-2009) it´s estimates that during the period January to March 2010 sulfur dioxide levels in the atmosphere would still be higher than the permitted levels.